DI-5-Cuffs: Bone Remodelling and Associated Metabolism Markers in Humans After Five Days of Dry Immersion to Simulate Microgravity - Linossier, Marie-Thérèse; Peurière, Laura; Fernandez, Peter; Normand, Myriam; Beck, Arnaud; Bareille, Marie-Pierre; Bonneau, Christine; Gauquelin-Koch, Guillemette; Vico, Laurence (Frontiers in Physiology, 2022)
Background: The dry immersion (DI) model closely reproduces factors of spaceflight environment such as supportlessness, mechanical and axial unloading, physical inactivity, and induces early increased bone resorption activity and metabolic responses as well as fluid centralization. The main goal of this experiment was to assess the efficacity of venoconstrictive thigh cuffs, as countermeasure to limit cephalad fluidshift, on DI-induced deconditioning, in particular for body fluids and related ophthalmological disorders. Our specific goal was to deepen our knowledge on the DI effects on the musculoskeletal events and to test whether intermittent counteracting fluid transfer would affect DI-induced bone modifications. Methods: Eighteen males divided into Control (DI) or Cuffs (DI-TC) group underwent an unloading condition for 5 days. DI-TC group wore thigh cuffs 8–10 h/day during DI period. Key markers of bone turnover, phospho-calcic metabolism and associated metabolic factors were measured. Results: In the DI group, bone resorption increased as shown by higher level in Tartrate-resistant acid phosphatase isoform 5b at DI24h. C-terminal telopeptide levels were unchanged. Bone formation and mineralization were also affected at DI24h with a decreased in collagen type I synthesis and an increased bone-specific alkaline phosphatase. In addition, osteocalcin and periostin levels decreased at DI120h. Calcemia increased up to a peak at DI48h, inducing a trend to decrease in parathyroid hormone levels at DI120h. Phosphatemia remained unchanged. Insulin-like growth factor 1 and visfatin were very sensitive to DI conditions as evidenced by higher levels by 120% vs. baseline for visfatin at DI48h. Lipocalin-2, a potential regulator of bone homeostasis, and irisin were unchanged. The changes in bone turnover markers were similar in the two groups. Only periostin and visfatin changes were, at least partially, prevented by thigh cuffs. Conclusion: This study confirmed the rapid dissociation between bone formation and resorption under DI conditions. It revealed an adaptation peak at DI48h, then the maintenance of this new metabolic state during all DI. Notably, collagen synthesis and mineralisation markers evolved asynchronously. Thigh cuffs did not prevent significantly the DI-induced deleterious effects on bone cellular activities and/or energy metabolism.